Comparative analysis of dermatoglyphic traits in Albanian and Turkish population living in Kosovo - Temaj, Gazmend (Array, 2009)
Abstract: The aim of the study was to compare quantitative dermatoglyphic traits of two ethnic groups with different origin and customs, living on the same territory. The dermatoglyphic prints were collected from 800 inhabitants of the Dukagjin valley in southwest Kosovo, of Albanian (400) and Turkish (400) ethnic origin. The quantitative analysis comprised the number of ridges and triradii on the fingers, and the number of ridges in the interdigital areas on the palm (a-b, b-c, and c-d) as well as the size of the atd angle. The statistical analysis showed significant differences between the Albanian and the Turkish males for two fingers and pattern intensity index left, and on palms for a-b rc and c-d rc on both hands and b-c rc on the left hand, and between females for six fingers and almost all palmar traits. Significant inter-population variations were observed for most palmar areas in both sexes but more pronouncedly in females. The differences found between the examined population groups show that admixture between Albanian and Turkish population in Kosovo has been small, and the Turks have retained their ethnic identity for several centuries